UTILIZING A GENOMIC DATABASE FOR IDENTIFYING GENOMIC VARIATION FOR SARS-CoV-2 RECEPTORS - Melodia Rezadhini; Lalu Muhammad Irham; Anisa Nova Puspitaningrum; Arief Rahman Afief; Wirawan Adikusuma; Dyah Aryani Perwitasari (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
Coronavirus disease 2019 (COVID-19) is a severe acute respiratory syndrome caused by the coronavirus SARS-CoV-2. This disease progresses through different stages, and its common symptoms include fever, malaise, dry cough, dyspnea, and pneumonia. Since its discovery in Wuhan, Hubei, China, in December 2019, SARS-CoV-2 transmission has rapidly spread. Unfortunately, the number of cases is increasing beyond expectations, making the spread of confirmed COVID-19 cases easier. To detect specific symptoms in a large population, the relationship between gene variants and patients with COVID-19 can be determined. The data of COVID-19 variations can be obtained from the Ensembl Genome Browser. Herein, the gene associated with 19 variants was selected according to the Haploreg 4.1 version. Additionally, protein expression of missense genes variants using the GTEx portal to determine 2 selected variants: rs200553089 encode the TLR7 gene and rs1061622 encode the TNFRSF1B gene, respectively. The highest protein expression of the TLR7 gene is found in lymphocyte cells, while TNFRSF1B shows the highest expression in the whole blood system. According to the data obtained from the Ensembl Genome Browser, the two most prevalent populations for SNP rs19085059, which is associated with the GPHN gene, are in Africa and East Asia, while SNP rs74956615, linked to the RAVER1 gene, is most prevalent in East Asia. The allele frequency for the TLR7 gene cannot be found in five countries, except in America. Keywords: COVID-19, SARS-CoV-2, Single nucleotide polymorphism, Variants.